Penggunaan Bahasa dan Tutur Kata Pedagang Dalam Melayani Visitor Konsumen pada Objek Wisata Situ Tandon Ciater, Kota Tangerang Selatan - Zulkarnain, Iskandar; Putranto, Ivan; Rovita, Angga (Indonesian Journal of Society Engagement, 2023)
The purpose of this community service (PkM) is to find out the use of language and speech of tandon tour traders in serving consumer visitors in South Tangerang. This service was carried out by the tourist attraction Situ Tandon Ciater. The service method uses lectures, discussions, and direct observation in the field. The participants of the activity were Tandon Ciater administrators and traders at TandonCiater tourist attraction. This service activity can be carried out well and can achieve the goals expected by the implementer. Based on the results of direct observation to the field, it is known that traders at Tandon Ciater tourism object, South Tangerang City do not have good communication, speech and language use skills. This can be seen when merchants communicate with buyers/consumers. Merchants need good communication training to serve consumers.